The Paris match - Clayborn, Kate (Berkley Romance, 2026)
"A woman tests the limits of her so-called amicable divorce when she flies to Paris for the destination wedding of her former sister-in-law, only to butt heads with the deliciously gruff best man, in a poignant and romantic novel from Kate Clayborn. Physician Layla Bailey has spent over a year telling herself she's moved on from a painful but amicable divorce from her college sweetheart. Staying friends with her ex seemed like the mature thing to do, but when Layla is invited to her former sister-in-law's destination wedding in Paris-where Layla once spent her own romantic honeymoon-she knows her commitment to maturity might be her worst enemy...especially since her ex isn't attending alone. The only thing that could make the week more difficult is getting through it without the distraction of the wedding.... But when what Layla thought was a harmless conversation about the choices of her younger self leads to the bride getting cold feet, Layla finds herself facing down the groom's mysterious, taciturn best man, Griffin, who will do anything to make sure this wedding happens. Since she broke it, Griff demands she help him fix it. Going along with his plan to alleviate the engaged couple's doubts seems like Layla's best chance at maintaining a good relationship with a family she once called her own. But as she learns more about the past heartbreak that's driving Griff to help his friend, she gets closer and closer to confronting the true depth of her own pain...while finding herself more and more willing to risk it all again for Griff"-- Provided by publisher.